What is community justice? case studies of restorative justice and community supervision - Karp, David R. 1964- (Pine Forge Press series in criminal justice., 2002)
As described in this title, the aim of the new efforts is to explicitly integrate the community and the criminal justice process in probation programs. There are five goals that this text addresses to achieve this end.